Pemberdayaan ibu hamil dalam pencegahan stunting melalui edukasi gizi berbasis emotional demonstration (EMO DEMO) - Febry, Fatmalina; Yuliana, Indah; Yuliarti; Sari, Desri Maulina; Ningsih, Windi Indah Fajar; Harwanto, Fatria; Ramadhani, Ira Dewi; Ramdika, Sari Bema; Ayun, Ayatussholikhah Qurrota; Fitriani; Nabilah, Defa Nuzul (Fakultas Kedokteran Universitas Sriwijaya, 2023)
Anemia has adverse health effects on pregnant women and their fetuses. Anemia during pregnancy will be at risk of giving birth to children with anemia leading to an increased risk of stunted children. EMO DEMO is a form of nutrition education with a simple delivery method developed by GAINing. (Global Alliance for Improved Nutrition). This community service aims to determine anemia in pregnant women and introduce EMO DEMO nutrition education to 30 pregnant women and 5 Posyandu cadres. The EMO DEMO material used food source high in iron named ATIKA (heart, fish, chicken). The activity was carried out in July 2022 in the village of Burai (Ogan Ilir) as stunting locus. The results of measuring hemoglobin levels found that as many as 8 pregnant women (26,7%) had anemia. Pregnant women and cadres found it easy to remember food ingredients that were good sources of iron during pregnancy. After participating in this EMO DEMO, it was expected participants could consume foods high in iron to prevent anemia during pregnancy. Furthermore, cadres could use the EMO DEMO method to conduct nutrition education for other pregnant women.